State and Trends of the Carbon Market—2004 - Lecocq, Franck (2012)
This study describes the status of the emerging carbon market, as of May 2004. The carbon market encompasses trades of greenhouse gas (GHG) emission allowances (under the European Union (EU) Emissions Trading Scheme), and project-based transactions, whereby a buyer participates in the financing of a project that reduces GHG emissions, compared with what would have happened otherwise, and gets emission reduction credits in exchange (for example, Clean Development Mechanism, or Joint Implementation projects under the Kyoto Protocol). The study finds that the carbon market is growing steadily. A total of 64 million metric tons of carbon dioxide equivalent (tCO2e) has been exchanged through projects from January to May 2004, nearly as much as during the whole year 2003 (78 million). Furthermore, the demand for emission reductions remains heavily concentrated, with a few EU governments, and Japanese firms the largest buyers. Finally, Asia is now the largest supplier of emission reductions, followed by Latin America, developed economies, and Eastern Europe. Prices of project-based emission reductions in early 2004 have remained essentially stable compared with 2003. In the absence of a standard contract, these prices strongly depend on the structure of the transaction, notably risk-sharing between buyers and sellers.